Pengembangan Potensi Daerah (Madu) Sebagai Desa Wisata Edukasi Coduzinc (Cookies Madu Zinc) - Nurul Amelinda Dwi Fatimah; Mar'atus Sholichah, Rizka (STIKES dan AKZI Karya Husada Kediri, 2024)
Kampung Madu is the Purworejo Hamlet nickname, located in Bringin Village, Badas District, Kediri Regency, East Java Province. The aim of the P2MD program for the Karya Husada Kediri Nutrition Academy Student Senate is to develop the potential of Kampung Madu by creating coduzinc educational tours and creating innovations in honey zinc cookies and being able to develop the potential of Kampung Madu. The methods used in this activity are location surveys, conducting outreach related to plans to develop the potential of the coduzinc educational tourism village, holding training on making coduzinc (honey zinc cookies), holding educational training on rice planting, holding educational training on bee farming, launching an educational tourism village, holding a coloring competition event, holding counseling on PHBS and hand washing, and conducting a test of acceptability of